Corporate IT security - Rydziński Patryk (My University, 2006)
Security is crucial issue in the case of company that distributes its business activities to different locations. This is mostly driven by the amount and value of data that needs to be shared in order to cooperate and coordinate the business activities. It is not that hard to imagine how dangerous it can be for a company and its environment to compromise a system holding important data or processes. The consequences might be severe, ranging from devastation of personal life or loss of money, assets and reputation or human life. Summing up, although globalization and relocation of resources brought huge amounts of benefits, the new model of business created many security threats too. Those threats can result in serious damage to an organization’s wellbeing and existence. In addition, organization compromise often influences not only the organization involved, but also its environment. Purpose of this document is to identify the most effective technologies, their weak and strong points as well as successful implementation methods. Document will also contain analysis of interactions of particular solutions as that seems to play an important role in system security. Having done all that I will try to determine if it is possible to create secure, complete, functional and economically acceptable system.
Bezpieczeństwo systemów informatycznych w przedsiębiorstwach
Keywords: information risk management; firewall; Virtual Private Networks; honeypots; Intrusion Detection Systems; Penetration Tests